Metode Pengajaran Penerjemahan Bahasa Arab - Muhammad Alang Wicaksono (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2021)
Language is an arbitrary sound symbol system used by members of social groups to work together, communicate, and identify themselves. Cross-language communication in the form of translation in the era of globalization still exists, and tends to be increasingly important. In the teaching and learning process, especially in the field of language, one of which is teaching tarjamah, in fact, it is not a new thing in the world of education and teaching in the field of language. There is no exception for translation activities from Arabic to Indonesian or vice versa. This translation has a goal, namely to produce a translation work that can present the meaning closest to the meaning of the source language. However, in the teaching process, teachers often encounter various problems. These problems are in the form of Mufrodat, tarkib in Arabic as well as the social condition of the language concerned which is to be translated. Given these various problems, it is necessary to study the method of teaching tarjamah from Arabic to Indonesian or Indonesian to Arabic.